2009
DOI: 10.1097/iae.0b013e318198d8de
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Congenital Toxoplasmosis Macular Scars With Optical Coherence Tomography

Abstract: The most characteristic OCT features in this young population were prominent retinal thinning, retinal pigment epithelium hyperreflectivity, and excavation of varying severity. OCT imaging is helpful in explaining better than expected vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 4 publications
3
20
0
Order By: Relevance
“…This structure conformed well to the findings of previous reports 25. On the other hand, the OCT features of congenital toxoplasmosis macular scars are retinal thinning, retinal pigment epithelium hyper-reflectivity, excavation, intraretinal cysts, and fibrosis 6,7. Added to the results of immunologic test, the OCT findings showed that the diagnosis of this patient was congenital macular coloboma.…”
Section: Discussionsupporting
confidence: 91%
“…This structure conformed well to the findings of previous reports 25. On the other hand, the OCT features of congenital toxoplasmosis macular scars are retinal thinning, retinal pigment epithelium hyper-reflectivity, excavation, intraretinal cysts, and fibrosis 6,7. Added to the results of immunologic test, the OCT findings showed that the diagnosis of this patient was congenital macular coloboma.…”
Section: Discussionsupporting
confidence: 91%
“…The most characteristic OCT features include prominent retinal thinning, retinal pigment epithelium hyper-reflectivity, and excavation of varying severity. OCT imaging has been found to be helpful in explaining better than expected vision [7].…”
Section: Discussionmentioning
confidence: 99%
“…Retinal thinning [169] RPE hyperreflectivity [169] Excavation [169] Intraretinal cysts [169] IS/OS inner segment/outer segment, RPE retinal pigment epithelium, ILM inner limiting membrane, IPL inner plexiform layer, BM bruch membrane, ELM external limiting membrane, ONL outer nuclear layer, FAF fundus autofluorescence, FA fluorescein angiography, ICGA indocyanine green angiography have parafoveal involvement or an intact neurosensory layer [169]. It has also been shown that OCT imaging can distinguish between active and scarred toxoplasmic lesions.…”
Section: Active Retinochoroidal Lesionmentioning
confidence: 99%